Q: Simplify expression 3 3z - 4 - 20 z - 5?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

3z-5

72xy^(3)

-47 + 6z = 3z-2-3z -3z-47 + 3z = -2+47 +473z = 45/3 /3z = 15

2b

-3z - 9 = 24 ⇒ -3z -33 = 0 (subtract 24 from both sides) ⇒ -33 = 3z (add 3z to both sides) ⇒ -11 = z (divide both sides by 3) ie z = -11

Related questions

If you mean: 33z-4-20z-5 then it is 13z-9 when simplified

3z-5

72xy^(3)

4-3 = 1

- - x + 3 = x + 3

Add like terms to like: (2z - 20) + (3z + 5) = (2z + 3z) + (-20 + 5) = 5z - 15 2z is shorthand for z+z, 3z is shorthand for z+z+z, so: 2z + 3z = (z+z) + (z+z+z) = z+z+z+z+z = 5z Or, to put it another way, just add the coefficients: 2z + 3z = (2+3)z = 5z.

3x+3-2x=3 x+3=3 x-0

-47 + 6z = 3z-2-3z -3z-47 + 3z = -2+47 +473z = 45/3 /3z = 15

(3+2i)-(3+2i)

2b

No

don't answer that